Prehistoric Modes of textual Production, or, books begat by other books - Beilharz, Peter (2011)
It all happened a long time ago. In 1975 a very serious book arrived from London. It was entitled Precapitalist Modes of Production, and its authors were Barry Hindess and Paul Q Hirst. It was hard work, though we were steeled for it by long hours spent with Althusser and Reading Capital as well as by reading Capital. No sooner had we finished this book, and puddled sideways through the accompanying journal Theoretical Practice, than another book arrived. It was called Mode of Production and Social Formation, and it was an autocritique of the first-mentioned book. There were invisible arrows in all this, and they pointed to Foucault rather than to Althusser, even if one of our authors was to follow that turn via political theory (Hindess) and the other, something more recognizably historicist (Hirst). As texts begat more texts (as medieval mice grew from moist cheesecloth) there were soon two more texts, these called Marx's "Capital" and Capitalism Today, and involving two more authors, Cutler and Hussain. In this article, I revisit this remarkable experience, hoping that our guest of honor might help throw light on this moment. © 2011 The Author(s).